Gender specific pharmacokinetic and pharmacodynamic considerations for antimuscarinic drugs for overactive bladder treatment. (1st February 2020) - Hartigan, Siobhan M.; Dmochowski, Roger R.
ABSTRACT: Introduction : Overactive bladder (OAB) has a heterogeneous presentation that varies between individuals and by gender. Treatment with antimuscarinic medications is standard first line pharmacotherapy for most patients with OAB. However, gender specific differences in the pharmacokinetics and pharmacodynamics of antimuscarinic therapy are often overlooked and not discussed. Areas covered : This review will explore differences by gender between the presentation and treatment of OAB. We will discuss the differences between sexes in terms of lower urinary tract anatomy, muscarinic receptors, and hormone variation. The effect of antimuscarinics on males and females as well as adherence and persistence patterns will be reviewed in order to fully review all available literature on the gender specific pharmacokinetic and pharmacodynamic considerations for antimuscarinic use in the treatment of OAB. Expert opinion : Despite extensive research into various antimuscarinic formulations and therapeutic regimens for the treatment of OAB, identification of gender specific pharmacokinetic and pharmacodynamics considerations remains scant. As our knowledge and understanding of OAB, muscarinic receptors, and antimuscarinic medications evolve, we will hopefully be better able to understand and implement gender-specific and genomic-sprecific treatment regimens and considerations for improved clinical outcomes.